A review of the Afrotropical Rhyssinae (Hymenoptera: Ichneumonidae) with the descriptions of five new species - Rousse, Pascal; Van Noort, Simon (European Journal of Taxonomy, 2014)
The Afrotropical Rhyssinae are reviewed. A total of 12 species are reported from the region, including five new species: Epirhyssa brianfisheri sp. nov., E. gavinbroadi sp. nov., E. shaka sp. nov., E. villemantae sp. nov. and E. tombeaodiba sp. nov. The generic status of E. brianfisheri sp. nov. is discussed since this species could also be considered to be an extra-limital Triancyra species, emphasizing the putative paraphyletic status of Epirhyssa. Epirhyssa ghesquierei Seyrig, 1937, E. overlaeti Seyrig, 1937 and E. uelensis Benoit, 1951 are newly reported from Cameroon. We provide illustrated diagnoses and identification notes. Finally, we discuss the apparent scarcity of African rhyssines compared to other regions.